Developmentalist and Political Instrumentalizations of African Cultural Heritage - (:unkn) unknown (My University, 2014)
Throughout the contemporary period, the heritage management process of the African cultural landscape has gone through constructions, deconstructions and ruptures in the elaboration of a national identity. Heritage instrumentalization in the interests of power (nation states, colonial empires) serves first as an ideological guarantee and then, for the purpose of development. Museums were the first actors of a political mechanism dedicated to the service of States, before gradually yielding to UNESCO the main role of North-South interlocutor in the cultural sector in order to build peace between nations. The World Heritage Convention (UNESCO, 1972) fosters an inscriptions policy of cultural properties integral to local identity. States concerned by this convention hope for socio-economic advantages for their territory, without always taking into account the local population.
Keywords: African Research